RELATIONSHIP OF MATERNAL MORBIDITY AND MORTALITY TO HIGH BODY MASS INDEX (BMI) PREGNANCIES IN PAKISTAN - Asra,; Riffat Jalil,; Shehla Arif, (Journal of Ayub Medical College Abbottabad, 2024)
Background: The average BMI is shifting upwards even in low-resource countries like Pakistan causing an increase in pregnancy-related complications. This study was planned to elaborate the association of maternal morbidity and mortality during pregnancy and puerperium with high BMI. Methods: A descriptive longitudinal study was performed in the Obstetrics and Gynaecology Unit 2 of D. Ruth K. M. Pfau Civil Hospital, Karachi, Pakistan from 1st August 2022 to 31st January 2023. Women delivering in Obstetric Unit 2 having a 1st-trimester record of weight were included. Demographic data, antenatal, intrapartum and postpartum complications noted. Participants were further stratified into 2 groups based on BMI i.e. overweight (25.0-29.9) and obese (30.0 or more) and demographics and clinical characteristics compared. Univariate and multivariate logistic regression analysis was done. Data was entered and analyzed on SPSS version 21. Result: The frequency is calculated to be 15.7%. The observed complications included pre-eclampsia 16.7%, PIH 13%, eclampsia 7%, GDM 18.9%, induction of labour 19.5%, PPH in 15.2% and infected caesarean wound in 19.2% of participants. The caesarean section was the predominant mode of delivery in 55.7%. A significant relationship was found with advancing maternal age, DM/ GDM, hypertension, Pre-eclampsia, IOL, caesarean section, PPH and wound infection. The univariate and multivariate logistic regression models also showed two times higher odd in obese groups as compared to overweight groups. Conclusion: Our study underscores a strong association between maternal obesity in early pregnancy and several threatening complications during pregnancy, delivery, and the postpartum period.